A comprehensive analysis of Italian web pages mentioning squalene-based influenza vaccine adjuvants reveals a high prevalence of misinformation - Donatella Panatto; Daniela Amicizia; Lucia Arata; Piero Luigi Lai; Roberto Gasparini (Taylor & Francis Group, 2018)
Squalene-based adjuvants have been included in influenza vaccines since 1997. Despite several advantages of adjuvanted seasonal and pandemic influenza vaccines, laypeople's perception of such formulations may be hesitant or even negative under certain circumstances. Moreover, in Italian, the term "squalene" has the same root as such common words as "shark" (squalo), "squalid" and "squalidness" that tend to have negative connotations. This study aimed to quantitatively and qualitatively analyze a representative sample of Italian web pages mentioning squalene-based adjuvants used in influenza vaccines. Every effort was made to limit the subjectivity of judgments. Eighty-four unique web pages were assessed. A high prevalence (47.6%) of pages with negative or ambiguous attitudes toward squalene-based adjuvants was established. Compared with web pages reporting balanced information on squalene-based adjuvants, those categorized as negative/ambiguous had significantly lower odds of belonging to a professional institution [adjusted odds ratio (aOR) = 0.12, p = .004], and significantly higher odds of containing pictures (aOR = 1.91, p = .034) and being more readable (aOR = 1.34, p = .006). Some differences in wording between positive/neutral and negative/ambiguous web pages were also observed. The most common scientifically unsound claims concerned safety issues and, in particular, claims linking squalene-based adjuvants to the Gulf War Syndrome and autoimmune disorders. Italian users searching the web for information on vaccine adjuvants have a high likelihood of finding unbalanced and misleading material. Information provided by institutional websites should be not only evidence-based but also carefully targeted towards laypeople. Conversely, authors writing for non-institutional websites should avoid sensationalism and provide their readers with more balanced information.